Hypoxia Blocks In Vivo Initiation of Simian Virus 40 Replication at a Stage Preceding Origin Unwinding - Riedinger, Hans-Jörg (American Society for Microbiology, 1999)
Simian virus 40 (SV40)-infected CV1 cells transiently exposed to hypoxia show a burst of viral replication immediately after reoxygenation. DNA precursor incorporation and analysis of growing daughter strands by alkaline sedimentation demonstrated that SV40 DNA synthesis began with a lag of about 3 to 5 min after reoxygenation followed by a largely synchronous viral replication round. Viral RNA-DNA primers complementary to the SV40 origin region were not detectable before 3 min upon reoxygenation. A distinct form of circular closed, supercoiled SV40 DNA was detectable as soon as 3 min after reoxygenation but not under hypoxia. Sensitivity to the DNA nuclease Bal 31 and migration behavior in chloroquine-containing agarose gels suggested that this DNA species was highly underwound compared to other SV40 topoisomers and was probably related to the highly underwound form U DNA first described by Dean et al. (F. B. Dean, P. Bullock, Y. Murakami, C. R. Wobbe, L. Weissbach, and J. Hurwitz, Proc. Natl. Acad. Sci. USA 84:16–20, 1987), in vitro. 3′-OH ends of presumed RNA-DNA primers could be detected in form U by 3′ end labeling with T7 polymerase. Addition of aphidicolin to the cells before reoxygenation led to a pronounced accumulation of form U DNA containing RNA-DNA primers. In vivo pulse-chase kinetic studies performed with aphidicolin-treated SV40-infected cells showed that form U is an initial intermediate of SV40 DNA replication which matures into higher-molecular-weight replication intermediates and into SV40 form I DNA after removal of the inhibitor. These results suggest that in vivo initiation of SV40 replication is arrested by hypoxia before origin unwinding and primer synthesis.